GOALS AND OBJECTIVESOF TEACHERS IN A CLASSROOM (Ustozlar uchun, 2025)
This article discusses the main goals and objectives of teachers in theclassroom. It emphasizes the importance of creating a positive and inclusive learningenvironment, promoting critical thinking, motivation, and continuous professionaldevelopment. The article highlights how teachers play a vital role in shaping students’intellectual and emotional growth through effective teaching and assessment strategies.